Numerical analysis of radial and angular stratification in turbulent swirling flames. (15th April 2019) - Sahebjamei, M.; Amani, E.; Nobari, M.R.H.
Abstract: In this work, a numerical approach is used to investigate the effects of level and type of stratification on turbulent methane-air stratified combustion. Two different scenarios are followed to create stratified conditions. In the first scenario, the Cambridge-Sandia flames which involve inhomogeneity in the radial direction are investigated. In the second scenario, a modification is applied to the inlet of the reference burner to study the effect of adding small- and large-scale non-homogeneities in the angular direction in addition to the radial one. The impacts of radial/angular stratified combustion on various flow fields such as velocity, temperature, H2, CO, and OH mass fractions are scrutinized. More importantly, the effects of radial/angular stratification on a series of global objective parameters, including combustion efficiency, maximum flame temperature, NO formation, CO and UHC emissions, entropy generation, and pattern factor at the outlet of the combustor are examined. It is manifested that adding a moderate level of small-scale angular stratification to the radial one would be beneficial in terms of combustion efficiency (42% increase with respect to the homogeneously premixed case) and pattern factor at the outlet of a combustor. Highlights: The effect of radial/angular stratification on flow field and performance parameters are studied. The combustion efficiency improves by 42% imposing a combined radial-angular stratified condition. Pattern factor is better in case of the combined stratification compared to purely radial stratified one. Maximum flame temperature rises with the presence of angular stratification but is independent of its level. Small-scale/large-scale angular stratification increases/decreases NO emission at the outlet.